2017
DOI: 10.1186/s12958-017-0296-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local endometrial injury in proliferative vs. luteal phase on IVF outcomes in unselected subfertile women undergoing in vitro fertilization

Abstract: BackgroundMechanical endometrial injury prior to IVF has been suggested as a means to increase implantation rates by improving endometrial receptivity. However, the effects of endometrial injury in proliferative vs. luteal phase have not been studied before. This study aimed to explore whether endometrial injury in the proliferative phase of the preceding cycle before in vitro fertilization/embryo transfer (IVF-ET) improves the clinical outcomes in unselected subfertile women compared with injury in luteal pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
126
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(131 citation statements)
references
References 30 publications
(27 reference statements)
1
126
1
3
Order By: Relevance
“…Since the publication of the abovementioned reviews, multiple RCTs on endometrial injury prior to ART have been carried out. While the first trials mainly focused on patients with RIF, more recent studies have shifted their focus to also include patients in earlier stages of IVF/ICSI treatment (Mahran et al , 2016; Liu et al , 2017; Tk et al , 2017; Maged et al , 2018). The increase in number of published studies not only calls for an updated review of the existing body of evidence, but also has created the possibility to subgroup patients according to the number of failed IVF/ICSI cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of the abovementioned reviews, multiple RCTs on endometrial injury prior to ART have been carried out. While the first trials mainly focused on patients with RIF, more recent studies have shifted their focus to also include patients in earlier stages of IVF/ICSI treatment (Mahran et al , 2016; Liu et al , 2017; Tk et al , 2017; Maged et al , 2018). The increase in number of published studies not only calls for an updated review of the existing body of evidence, but also has created the possibility to subgroup patients according to the number of failed IVF/ICSI cycles.…”
Section: Introductionmentioning
confidence: 99%
“…compared performing EI in the luteal phase and in the proliferative and suggested that there was no significant difference in terms of clinical outcomes . We believe performing EI in the proliferative phase may influence the characteristic and function of the proliferative endometrium. On the other hand, performing EI on the third day of the menstrual cycle may promote epithelial cells and stromal cells proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Yeung, et al [14] however, did not test a homogeneous population of IVF patients with RIF. Even more concerning was the fact that participants in this study as well as in the study by Liu, et al [15] were subjected, prior to the endometrial biopsy, to either Saline Infusion Sonogram (SIS) or hysteroscopy. These procedures, on their own, could cause mechanical injury that may positively affect endometrial receptivity, leaving no potential for benefi cial effect of the biopsy.…”
mentioning
confidence: 93%